Therapeutic efficacy of artemether-lumefantrine plus single low dose primaquine for the treatment of uncomplicated Plasmodium falciparum malaria in a high transmission setting, Western Ethiopia - Jimma Dinsa Deressa; Sinknesh Wolde Behaksra; Eshetu Molla; Alemayehu Letebo; Girma Shumie; Bethlehem Adnew; Dawit Hailu Alemayehu; Fikregabrail Aberra Kassa; Tamrayehu Seyoum; Elias B. Tafa; Kidist Woldekidan; Legesse Alamerie Ejigu; et al. (PLoS ONE, 2026)
Background The development and spread of drug-resistant parasites continue to threaten progress toward malaria elimination. Therapeutic efficacy and molecular resistance marker studies are needed to guide national control programs. In African settings, evidence of partial resistance to artemisinin-based combination therapies (ACTs) associated with Pfkelch13 mutations is accumulating, and World Health Organization (WHO) recommends regular monitoring of first line antimalarial drugs for early detection of resistant parasites. In this study, we evaluated the efficacy of artemether-lumefantrine (AL) combined with a single low dose of primaquine (PQ) for treating uncomplicated Plasmodium falciparum malaria in a co-endemic area where P. falciparum predominates. Methods and findings One hundred twenty-three patients with P. falciparum mono-infection were enrolled between November 2020 to March 2021 and treated with artemether-lumefantrine (AL) plus a single low dose of primaquine (PQ) as per the national malaria treatment guideline and followed up for 28 days. Ethical approval was obtained from the AHRI/ALERT ethics committee (Po/23/19), and the study was registered at Pan-African clinical trials registry (PACTR) with unique identification number of PACTR202509595696440. Pfmsp2 capillary electrophoresis (CE) genotyping was used to differentiate recrudescence from new infections. More than half (56.1%) of the participants had high parasitemia (>10,000 parasites/μL) at enrollment. On day 3, 16.9% (20/118) remained parasitemic, and of the 10 individuals with detectable gametocytes at enrollment, only 3.4% remained gametocytemic on day 3, and 100% parasite clearance was observed on day 7, respectively. Multiplicity of infection was 3.8 at enrollment and 1.7 at the time of recurrence. The adequate clinical and parasitological responses at 28-day (ACPR) of per protocol analysis (PPA) was 73.7% for PCR-uncorrected and 91.3% for PCR-corrected, respectively and while, the intention-to-treat analysis (ITA), the Kaplan–Meier estimated treatment success at day 28 was 93.2% (95% CI: 88.5–98.2) after PCR correction, compared with 78.3% (95% CI: 71.0–86.4) in the PCR-uncorrected analysis. In our study assessment, no cases of severe malaria or serious adverse events occurred. Conclusions The efficacy observed in this study, although remaining above the WHO policy change threshold after PCR correction, may indicate a potential decline in AL’s effectiveness in this high transmission setting. However, because antimalarial drug concentrations were not measured and evening doses were not fully directly observed, reduced drug exposure or imperfect adherence cannot be excluded as possible contributors to the observed treatment outcomes Therefore, we suggest regular therapeutic efficacy monitoring and further investigation using advanced molecular techniques, such as next-generation sequencing (NGS), to enable early detection of resistance-associated parasite variants that may compromise treatment efficacy.